The quality of the Bahasa Indonesia-English-Arabic constitution of the Republic of Indonesia multilingual translational - Afif Suaidi (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2017)
This research is aimed to know the quality of Bahasa Indonesia, English, and Arabic UUD 45 MTTs in terms of meaning accuracy, meaning clarity, and expression naturalness and to explain the factors that motivate the quality. This is qualitative research type which employs a content analysis method specifically semantic content analysis and grammatical content analysis. The data are clause unite in the Bahasa Indonesia, English, and Arabic UUD 45 MTTs. Research results show that the quality of Bahasa Indonesia – English UUD 45 TT falls into a ‘good’ category and the quality of Bahasa Indonesia – Arabic UUD 45 TT falls into a ‘very good’ category. The degrees of quality of MTTs in T2 consist of ‘less accurate meaning’ category, ‘very clear meaning’ category, and ‘very natural expression’ category. The degrees of quality of MTTs in T3 consist of ‘less accurate meaning’ category, ‘very clear meaning’ category, and ‘very natural expression’ category. The factors that motivate the quality are inaccurate meaning, unclear meaning, and unnatural expression.